2012
DOI: 10.1111/j.1399-3046.2012.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment in children following kidney transplantation

Abstract: CV diseases are the leading cause of death among patients with ESRD. RTX decreases the CV risk; however, it still remains definitely higher than that of the general population. Large multicenter and longitudinal studies are difficult to perform and hard end-points of CV events are usually missing among pediatric population. Thus, appropriate estimation of CV risk is of crucial importance to define the potential hazards and to evaluate the effect of treatments aimed to reduce the risk. A number of validated non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 118 publications
(163 reference statements)
1
19
0
Order By: Relevance
“…Even then, because these patients have a significantly longer life expectancy than adult KT recipients, the propensity for early discovery and reduction of CVD manifestations on this population is of greater importance. While transplant care—immunosuppression, rejection and infection surveillance, cancer screening, renal function, and blood pressure management—in these patients is much more comprehensive, the overlap between disciplinary lines is less exhaustive for cardiovascular screening and health maintenance . Thus, in moving forward, the programmatic schema for the reduction in CVEs in pediatric KT recipients must entail aggressive implementation of conventional treatment and surveillance guidelines such as frequent cardiac rhythm assessment, low dose aspirin, and statin administration.…”
Section: Discussionmentioning
confidence: 99%
“…Even then, because these patients have a significantly longer life expectancy than adult KT recipients, the propensity for early discovery and reduction of CVD manifestations on this population is of greater importance. While transplant care—immunosuppression, rejection and infection surveillance, cancer screening, renal function, and blood pressure management—in these patients is much more comprehensive, the overlap between disciplinary lines is less exhaustive for cardiovascular screening and health maintenance . Thus, in moving forward, the programmatic schema for the reduction in CVEs in pediatric KT recipients must entail aggressive implementation of conventional treatment and surveillance guidelines such as frequent cardiac rhythm assessment, low dose aspirin, and statin administration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that focused on the cardiovascular benefits that transplantation provides have shown that transplantation early in ESRF reduces the known cardiovascular risk factors associated with chronic kidney disease and long term dialysis [11]. Cardiovascular disease is responsible for the deaths of 36% of all children with end stage renal failure, 34% of those on dialysis and 11% of paediatric deaths after transplantation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Given these effects are related to the tacrolimus dose and concentration, Tac-OD may have beneficial effects on glucose metabolism and blood pressure due to low peak concentration compared with Tac-BID (26)(27)(28). In the clinical perspectives, these positive effects are quite important because cardiovascular disease is a leading cause of death after kidney transplantation in pediatrics as well as adults (29,30). Considering that Tac-OD can improve patient adherence to immunosuppressants by reducing barriers to adherence (Table S1), the beneficial effects of Tac-OD in the long-term outcome is certainly worth investigating.…”
Section: Once-daily Tacrolimus In Pediatric Patientsmentioning
confidence: 99%